2021
DOI: 10.1071/sh20197
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus infection in HIV-infected men in Singapore, 2006–2018: incidence and associated factors

Abstract: Background: The epidemiology of hepatitis C virus (HCV) infection in people living with HIV has been evolving, with increasing evidence of permucosal (sexual) transmission identified predominantly in HIV-positive men who have sex with men (MSM). The aim of this study was to estimate the incidence rate and elucidate epidemiological factors associated with HCV infection among HIV-infected men in Singapore from 2006 to 2018. Methods: A retrospective cohort study was conducted using a clinical database maintained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 53 publications
(73 reference statements)
0
1
1
Order By: Relevance
“…The incidence rates of HIV/HCV co-infection in some Asian and European countries were lower than that reported in this study with a rate of 0.88 per 100 person-years in Singapore, 19 and 0.72 and 0.44 per 100 person-years among MSM in France 20 and Italy 21 . A systematic review conducted between 2000 and 2016 reported an incidence rate of 0.78 per 100 person-years among MSM.…”
Section: Discussioncontrasting
confidence: 83%
“…The incidence rates of HIV/HCV co-infection in some Asian and European countries were lower than that reported in this study with a rate of 0.88 per 100 person-years in Singapore, 19 and 0.72 and 0.44 per 100 person-years among MSM in France 20 and Italy 21 . A systematic review conducted between 2000 and 2016 reported an incidence rate of 0.78 per 100 person-years among MSM.…”
Section: Discussioncontrasting
confidence: 83%
“…In the Asia-Pacific region, the prevalence of HCV co-infection among adult PLHIV ranges from 2.9% to 80% depending on the characteristics of the study population [4][5][6][7][8][9][10][11][12]. Injecting drug use is consistently associated with an increased risk of HCV coinfection, [10,[13][14][15][16] and men who have sex with men (MSM) and sex workers living with HIV are also at increased risk [17,18]. Other factors associated with HCV coinfection among Asian adult PLHIV include older age, lower education [19], lower CD4 cell count [4,20], and having a household member with liver disease [21].…”
Section: Introductionmentioning
confidence: 99%